Information Management System among the Vegetable Growers in Western Uttar Pradesh - Singh, Dan; Yadav, R. N.; Singh, D.K.; Shanti, Kumari (Indian Journal of Extension Education, 2018)
Most of the vegetable growers had a high level of information management. The sources like friends, television,  progressive farmers, input suppliers, newspapers, mitra krishak/sampark krishak and University Scientists were found to  the most credible sources of information. More than 50 per cent package of practices completely utilized by the vegetable  growers. The higher satisfaction index percentage was found in harvesting and lowest in use of micro-nutrient /plant  growth regulator.
Keywords: Information management system and vegetable growers